Correlation between the arm-span and the standing height among males and females of the Khasi tribal population of Meghalaya state of North-Eastern India - Amitav Sarma; Bhupen Barman; Gautam C Das; Hiranya Saikia; Ambath D Momin (Journal of Family Medicine and Primary Care, 2020)
Introduction: The estimation of relationship between the arm span and the standing height has been an important tool in anthropometric measurements especially in cases where direct measurement of stature is not possible. Objective: To find the relationship between the arm-span and the standing height of both males and females in the population of Khasi tribal population of Meghalaya. Materials and Methods: The study involved 400 numbers (272 males and 128 females) of healthy human volunteer subjects belonging to Khasi tribe of Meghalaya. The standing height and arm-span were measured for each individual and analyzed. Result: Of the 400 healthy volunteers, 272 (68%) were males and 128 (32%) were females with age ranged from 25 to 45 years. Height and arm span in males (159.68 ± 4.12 cm and 166.30 ± 4.27 cm, respectively) werefound to be significantly (p < 0.001) higher than females (149.96 ± 3.04 cm and 155.77 ± 3.13 cm respectively). The Pearson correlation coefficient (r) between height (cm) and arm span (cm) showed significant positive correlation in both male (r = 0.988, P < 0.001) and female (r = 0.991, P < 0.001) study subjects. The regression equation was Height = 1.060 + 0.954 (Arm span); R2 = 0.976; SEE = 0.646 for male. For female subjects the regression equation was found as Height = 0.150 + 0.962 (Arm span); R2 = 0.983; SEE = 0.400. Conclusion: Arm-span can be used as one of the most reliable parameter in both males and females for obtaining the stature of an individual in alternative to the height.